The Tumor Suppressor Kruppel-Like Factor 6 Is a Novel Aryl Hydrocarbon Receptor DNA Binding Partner - Wilson, Shelly R.; Joshi, Aditya D.; Elferink, Cornelis J. (The Journal of pharmacology and experimental therapeutics, 2013)
The aryl hydrocarbon receptor (AhR) is a ligand-mediated basic helix-loop-helix transcription factor of the Per/Arnt/Sim family that regulates adaptive and toxic responses to a variety of chemical pollutants, including polycyclic aromatic hydrocarbons and halogenated aromatic hydrocarbons, most notably 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Ligand activation leads to AhR nuclear translocation and binding to a xenobiotic response element (XRE) in association with the Arnt to regulate gene expression. Several recent genome-wide transcriptional studies identified numerous AhR target genes that lack the canonical XRE recognition site in the promoter regions. Characterization of one such target gene, the plasminogen activator inhibitor 1, identified a novel nonconsensus XRE (NC-XRE) that confers TCDD responsiveness independently of the Arnt protein. Studies reported here show that the NC-XRE is a recognition site for the AhR and a new binding partner, the Kruppel-like factor (KLF) family member KLF6. In vivo chromatin immunoprecipitations and in vitro DNA binding studies demonstrate that the AhR and KLF6 proteins form an obligatory heterodimer necessary for NC-XRE binding. Mutational analyses show that the protein-protein interactions involve the AhR C terminus and KLF6 N terminus, respectively. Moreover, NC-XRE binding depends on the 5′ basic region in KLF6 rather than the previously characterized zinc finger DNA binding domain. Collectively, the results unmask a novel AhR signaling mechanism distinct from the canonical XRE-driven process that will enrich our future understanding of AhR biology.